Erosion of Uttar Pradesh Soils by Water and its Relation to Soil Properties - Verma, Anupam (Journal of Soil and Water Conservation, 2022)
The study of soil erosion by water in the laboratory has been done very little in India specially with Uttar Pradesh soils. In the field scale, however, Bhattacharjee (1957) and Mehta, Mathur and Shankernarayana (1958) among others made some notable contribution on the erosion of West Bengal and Kota soils respecti-vely. They correlated their erosion studies with the different physico-chemical properties of soil samples used by them. It was therefore, thought fit to extend the work in a laboratory scale with a few U.P. soils on which similar works are not available.